Financial Performance of a Regional Water Utility: The Role of Good Corporate Governance, Liquidity, and Operational Efficiency - Pora, Alfian A.N.; Soleman, Rusman; Zamzam, Irfan (International Journal of Economics, Business and Innovation Research, 2026)
This study aims to analyze the role of Good Corporate Governance (GCG), liquidity conditions, and operational efficiency in reflecting financial performance at the Ake Gaale Regional Water Supply Company in Ternate City. Regional State-Owned Enterprises (BUMDs) play a strategic role in providing public services while also being expected to maintain sustainable financial performance. However, various regional water supply companies still face challenges related to operational efficiency, financial management, and corporate governance. This study employs a qualitative descriptive approach using secondary data in the form of financial statements and corporate governance documents for the period 2019–2024. The data analysis techniques used include descriptive analysis, financial ratio analysis comprising the Current Ratio (CR), the Operating Expense to Operating Revenue Ratio (BOPO), and Return on Assets (ROA), as well as trend analysis. The results indicate that the implementation of GCG falls into the “highly reliable” category, with an index value ranging from 90% to 100%. The company’s liquidity level is classified as very high, with a CR ranging from 361% to 766%; however, this condition is largely influenced by high accounts receivable. Operational efficiency, as measured by BOPO, shows fluctuating conditions, while financial performance, as measured by ROA, shows a downward trend after 2019. The findings of this study indicate that the implementation of strong governance and liquidity does not necessarily lead to improved financial performance if operational efficiency is not yet functioning optimally.